Amplitude Versus Time Resolution Trade-Off in Digital RF Transmitter Line-Ups - Wiedemann, Jan Philipp Wiedemann; Fischer, Georg; Irnstorfer, Florian (2024 15th German Microwave Conference (GeMiC), 2024)
A novel power amplifier (PA) architecture is presented which constitutes a hybrid between the switched capacitor PA (SCPA) and the class-D PA in order to improve the transmitter line-up digitization for high power radio frequency (RF) applications. Instead of using either the amplitude (corresponding to the SCPA) or the temporal (corresponding to the class-D PA) resolution to reconstruct the desired output signal amplitude, a trade-off between the two possibilities is used in order to relax the requirements for both. This work derives the theoretically optimum drive signals needed to realize such an architecture showing that the optimum drive strategy enables high signal integrity and power efficiency at high power RF output signals, while requiring fewer high speed drive signal generation circuits than initially expected.
CRIS-Team Scopus Importer:2024-04-26
Keywords: class-D; hybrid PA; Power amplifier; SCPA; Switched capacitor PA